E-Management Capability for Future Government Organizations in UAE - Rashid Almansoori, Wadha Hamad Mohamed; Ahmad, Suraya; Al-shami, Samer Ali (Opción, 2019)
E-management embarks utilization on Information Technology (IT) to aug- ment the management of government organization by modernized organiza- tion processes and revamp the flow of information within a government or- ganization. E-management is the activities of an organization processes on the internet that embrace a diversity of functions and services. The broadening of e-management in recent decades has given rise to a new government or- ganization’s requirements in the UAE. The key intention of this research was to confer e-management capability is important for future government or- ganizations in the UAE. The major research question was whether e-manage- ment capability influences future government organizations in the UAE. This study intends to yield key drivers of e-management capability that influence future government organizations in the UAE. Yet, e-management emphasizes on value creation through integrating IT with traditional processes. The re- search key results pivot on developing the conceptual model of key drivers of e-management capability that influence future government organizations in the UAE.